ANALISIS PERENCANAAN SUMBER DAYA MANUSIA (HUMAN RESOURCES PLANNING) PADA LEMBAGA ADMINISTRASI NEGARA DI JAKARTA - Agnes Madeline Esti; Herbasuki Nurcahyanto; Aufarul Marom (Journal of Public Policy and Management Review, 2021)
The State Administration Agency (LAN) is an agency that has the authority to foster functional positions, especially policy analysts and improve the quality of bureaucracy government in Indonesia. The purpose of this research is to analyze human resource planning at the State Administration Institute. This study uses a qualitative descriptive approach. Data collection techniques were carried out using literature study and interview methods. Determination of informants in the interview technique is to use purposive sampling. Human resource planning at the State Administration Institute from the results of the author's research analysis, it can be concluded that the process has been running quite well. This can be seen from the application of Governmental Regulations No. 11 of 2017, Head of LAN Regulation Number 2 of 2019 concerning HR Management and Minister of Administrative and Bureaucratic Reform No. 3 of 2020. The obstacles faced in the recruitment process for LAN employees are technical problems and data integration. Suggestions that can be given by researchers are the need for making a flowchart of human resource planning in LAN and innovation in human resource development strategies for LAN employees.